KONTRIBUSI KECERDASAN SPASIAL VISUAL DAN KOMPETENSI PROFESIONAL GURU TERHADAP HASIL BELAJAR MATA PELAJARAN DESIGN GRAFIS JURUSAN MULTIMEDIA SMKN 1 KEC.LUAK KAB. LIMA PULUH KOTA - Ameliza Desti; Putra Jaya; Nelda Azhar (Universitas Negeri Padang, 2014)
This research was intended to disclose the extent to which the spatial visual intelligence and the teacher’s professional competence contributed either independently or simultaneously toward the students’ learning achievement. The population of the research was the students in class X of SMKN 1 Kecamatan Luak Kabupaten Lima Puluh Kota that consisted of 65 students. By using simple random sampling technique, 40 students then were taken as the sample. The data in the form of the students’ learning achievement was gotten from the teacher of graphic design majoring in Multimedia. Meanwhile the data of the students’ spatial visual intelligence and the teacher’s professional competence was gotten through questionnaires administered to the students. The result of the research indicated that (1) the spatial visual intelligence and the teacher’s professional competence simultaneously contributed significantly (30,8%) toward the students’ learning achievement, (2) the spatial visual intelligence contributed significantly (17,8%) toward the students’ learning achievement, and (3) the teacher’s professional competence contributed significantly (10,6%) toward the students’ learning achievement. Based on these results, it was concluded that the spatial visual intelligence and the teacher’s professional competence had a contribution toward the students’ learning achievement in SMKN 1 Kecamatan Luak Kabupaten Lima Puluh kota. Kata Kunci :Kecerdasan Spasial Visual, Kompetensi Profesional Guru, Hasil Belajar